Airflow obstruction is associated with increased smooth muscle extracellular matrix. Issue 6 (17th March 2016) - Jones, Robyn L.; Noble, Peter B.; Elliot, John G.; Mitchell, Howard W.; McFawn, Peter K.; Hogg, James C.; James, Alan L.
Increased thickness of the airway smooth muscle (ASM) layer is a characteristic feature of airway remodelling in both asthma and chronic obstructive pulmonary disease (COPD) [1, 2]. The composition of the ASM layer has been well studied in asthma where the increased thickness of the ASM layer is due to hypertrophy and/or hyperplasia [3–5] of ASM cells. These changes are associated with a concomitant increase in absolute volumes of both ASM and extracellular matrix (ECM), without changes in their relative volume fractions [5]. Although ASM cell hypertrophy has been reported in the large airways of patients with COPD [6], these findings did not exclude the effect of an increase in the volume fraction of ECM on the estimated average volume of the ASM cells [7]. Remodelling of the layer of airway smooth muscle in COPD is characterised by an increase in the extracellular matrix http://ow.ly/YZqhz